An exploration of factors contributing to gang membership - Waugh, Alison (2017)
Attempts have been made to theoretically and empirically identify which factors drive gang-joining approaching a century, however a synthesis of the research which might guide future research is lacking, as is whether these are different to their non-gang counterparts. Perhaps more surprisingly, researchers have highlighted gender differences between gang-members but a large proportion of the research does not control for this. This thesis addresses the above points, specifically looking at individual risk factors for male gang-membership; violence, delinquency, personality, psychopathy, cognitive factors, externalizing and internalizing-behaviours, self-esteem, negative life-events, and limited opportunities. Statistical analysis evidenced factors which might be risk factors for (violence, delinquency, and externalizing-behaviours) and consequences of gang-membership (internalizing-behaviours), as well as those which may be exacerbated by gang-membership (violence and delinquency). This thesis highlights a need to shift the research focus to the negative consequences of gang-joining. A first of its kind, this thesis also examines the role of adult attachment within the gang showing that gang-members were less anxious in their friend attachments and therefore a possible protective function of the gang, which will have implications for gang-desistence strategies. Inconsistency about the role of self-esteem in gang-membership appears to still remain, however this may be attributed to differences between implicit (unconscious) and explicit (unconscious) reporting of self-esteem, lack of clarity about whether it is high or low self-esteem that is associated with violence, uncertainty about whether the gang boosts or reduces self-esteem, as well as differences in study design. Unfortunately this thesis was not able to clarify this ambiguity, an attempt to explore the use of an implicit self-esteem measure suggests that this has preceded a reliable and valid definition of implicit self-esteem and some possible areas for future research.